Energy forests or vineyards? - Koncz, Gábor; Kozsdáné Bata, Mária; Szabóné Pap, Hajnalka (Acta Agraria Debreceniensis, 2010)
This paper primarily aims at giving an introduction to an alternative opportunity for vineyards owners many of whom have come to adecision about elimination of their vineyards. The paper is focusing on the Mátra wine-region as a study area, which is the largest mountainwine region in Hungary where more than one third of supported clearing of vineyards have been implemented in the last few years. Theabandoning of vineyards is explicable in more than one way such as very small average size of land or the increasing mean age of ownersetc. The fundamental reason is the chronic doubtfulness of the grape and wine market and the low level of overall profitability of production.Grape production has a long tradition in this region, thus the disappearance of vineyards caused serious problems in land use through theabsolute lack of plans for the future. The popularity of biomass production in the press and the biofuel resultant from vine stocks raiseinterest for short rotation forestry within a group of farmers. Short rotation forestry offers a new chance for some farmers to cut oneself adriftfrom the harmful effects of the market of agricultural products.